Innovation as a knowledge-based outcome - Quintane, Eric; Casselman, Mitch; Reiche, Sebastian; Nylund, Petra (Journal of Knowledge Management, 2011)
Purpose - The purpose of this paper is to provide clarity to the concept of innovation and its various definitions.Design/methodology/approach - The article reviews the innovation literature and proposes that innovation has been conceptualized either from a process or from an outcome perspective. Also, the authors show that there is a substantive difference between innovation seen in the traditional innovation literature and innovation as conceived in the knowledge management literature.Findings - The paper proposes a general framework to categorize the existing views of innovation and show that innovation as an outcome has not been clearly defined from a knowledge perspective. To address this gap, the authors develop a new definition of an innovation outcome based on knowledge elements.Research limitations/implications - The research lays the groundwork for more comprehensive methods of measuring innovation and innovativeness, which is particularly useful for the study of service innovation.Practical implications - The framework and definition expand the ability of managers to measure and understand the key factors of innovation.Originality/value - The research contributes to the literature by developing a comprehensive knowledge-based, outcome-oriented definition of innovation.
Keywords: Innovation; Knowledge; Process; Outcome; Definition; Knowledge management